Sound velocities for hexagonally close‐packed iron compressed hydrostatically to 136 GPa from phonon density of states. Issue 12 (19th June 2013) - Gleason, A. E.; Mao, W. L.; Zhao, J. Y.
Abstract: [1] The phonon density of states of pure iron ( 57 Fe) was measured under hydrostatic conditions using nuclear resonant inelastic X‐ray scattering (NRIXS) at pressures up to 136 GPa. Extracting shear ( Vs ) and compressional ( Vp ) wave speeds from the Debye velocity and equation of state, we find the hydrostatic shear wave speed trend above previously collected NRIXS data under nonhydrostatic conditions by roughly 5%–6% in the measured pressure range. Using the Birch Murnaghan finite strain approach to fit pressure‐dependent adiabatic bulk and shear moduli, we extrapolated our velocities to inner Earth core densities and found that our shear wave speeds are 3% higher than those in previous studies. Our results on pure iron provide a more accurate and precise baseline to which added complications (e.g., Ni concentration, inclusion of various light elements, and temperature effects) can be considered when comparing experimental elasticity measurements to inner core seismic data. Key Points: velocities to inner Earth core densities are more accurate provides a better baseline